How to Write a Better Thesis - Evans, David; Gruba, Paul.; Zobel, Justin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
From proposal to examination, producing a dissertation or thesis is a challenge. Grounded in decades of experience with research training and supervision, this fully updated and revised edition takes an integrated, down-to-earth approach drawing on case studies and examples to guide you step-by-step towards productive success. Early chapters frame the tasks ahead and show you how to get started. From there, practical advice and illustrations take you through the elements of formulating research questions, working with software, and purposeful writing of each of the different kinds of chapters, and finishes with a focus on revision, dissemination and deadlines. How to Write a Better Thesis presents a cohesive approach to research that will help you achieve your goals.   David Evans was Reader and Associate Professor in the Faculty of Architecture Building and Planning, University of Melbourne. Paul Gruba is Senior Lecturer in the School of Languages and Linguistics, University of Melbourne. Justin Zobel is Professor in the Department of Computing and Information Systems, University of Melbourne.
What is a Thesis? -- Thesis Structure -- Mechanics of Writing -- Making a Strong Start -- The Introductory Chapter -- Background Chapters -- Establishing Your Contribution -- Outcomes and Results -- The Discussion or Interpretation -- The Conclusion -- Before You Submit -- Beyond the Thesis.
Keywords: elektronické knihy; electronic books; Computer science; Learning, Psychology of; Natural language processing (Computer science).; Engineering; Life sciences; Social sciences; Humanities; Computer Science; Instructional Psychology; Natural Language Processing (NLP).; Technology and Engineering; Life Sciences; Humanities and Social Sciences